IMPLEMENTATION OF BINARY LOGISTIC ANALYSIS ON DETERMINANTS OF MALARIA STATUS - Sigit Budiantono; Dyah Purwanti; Nurhidayati Nurhidayati; Pardomuan Robinson Sihombing; Ade Marsinta Arsani (LPPM Universitas Bina Bangsa, 2023)
Malaria is a disease transmitted through mosquitoes; malaria is still one of the endemic diseases in Eastern Indonesia. This study aims to determine the factors that affect malaria status. The independent variables used were region, gender, insect repellent, sowing larvicide powder, draining the bathtub, and mosquito nets. The data comes from the Basic Health Research Report (Riskesdas) 2018. The analysis method used is binomial regression / binary logistics. Based on research states that together all independent variables have a significant effect on a person's malaria status. Partially, the chances of rural status, male sex, not using insect repellent, not using larvicide powder, not draining bathtubs, and not wearing mosquito nets are greater than other categories of malaria status. Therefore, self-awareness of individuals and communities is needed in striving for cleanliness and personal health